Maternal And Fetal Outcome in Placenta Previa: A Multicenter Prospective Observational Study - Beenish Khan; Syeda Surayya Jabeen; Fatima Sharif Khan; Faria Mumtaz; Reema Gul; Qudsia Nawaz (Journal of Rawalpindi Medical College)
Objective: To find out the frequency of placenta previa and maternal and fetal outcomes in cases of placenta previa in our population.